Thursday
March 30, 2017

Post a New Question

Posted by on .

derivative of f(x) = x/(sqrt(x^2-4))

  • calc - ,

    I would rewrite it as
    y = x(x^2 - 4)^(-1/2_
    then use the product rule

    dy/dx = x(-1/2)(x^2-4)^(-3/2)(2x) + (x^2-4)^(-1/2)
    we could factor that

    dy/dx = (x^2-4)^(-3/2)[-x^2 + x^2-4]

    = -4/(x^2-4)^(3/2)

    check my work, I did not write it on paper first, did all the steps as I typed.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question